Kazan and Moscow : five centuries of crippling coexistence under Russian imperialism (1552-2002) : from Ivan, Lenin, Stalin, Gorbachev, Shaimiev, Yeltsin to Putin. - Daulet, Shafiga. (New Hampshire)
xvi, 826 s.